May the procrastination be a health problem? (Brazilian Journal of Behavioral and Cognitive Therapy, 2001)
Taking into account that health prevention is a current problem and it may be connected to procrastination, it was investigated whether people are used to delay medical tests and/or health care, the reasons for such delay, what they think about this specific delay. Thirty-one subjects were interviewed, ages between 18 and 67 years old, 16 females and 15 males. They verbally answered the questions and the interviewer took notes. Results show that, among the reasons given to delay medical tests, are: other priorities, a lack of information and consciousness about prevention and the time spent on it. Check-ups and prevention of gynecological cancer are considered prior tests. 16 out of 31 admitted the delay. Similarities with the habit of studying and everyday life are discussed.